Peningkatan Tanggung Jawab Belajar Matematika Melalui Strategiproject Based Learning PadaSiswaKelas VII Semester Genap SMP Muhammadiyah 1 Surakarta TahunAjaran 2014/2015 - Santi, Fifin Kurnia; , Prof. Dr. Sutama, M.Pd (2015)
The purpose of this research was to improve the responsibility of studying mathematics through Project Based Learning strategy to students class VII A SMP Muhammadiyah 1 Surakarta. This kind of research was a classroom action research. This research used descriptive qualitative method so the purpose of this research could be reached researcher's hope. This research method was coducted through collaboration process among the mathematics teacher, the headmaster, and the researcher. This form research was cycle, every cycle was consist of four prime activity,they were (1) plan, (2) act, (3) observe, and (4) reflect.This students of class VII A were as recipients subject, the teacher was as the subject of action giver. The data collecting method were observation, interview, field note, and documentation. Data analysis technique were data reduction, data presentation,and verification. The result of this research was improving the responsibility of studying mathematics that can be saw from this indicators, they were: 1) finished the task without copy (did for the job seriously), before the action, there were 10 students (38,46%),after the action there were 23 students (92%); 2) they were braving to say their opinion or presenting the result of their work team (executed and could explain the information that they got from the commanded task), before the action there were 12 students (46,15%), after the action there were 20 students (80%). Based on the text could be concluded that the applying of Project Based Learning strategy could be improving the responsibility of studying mathematics.